MENINGKATKAN HASIL BELAJAR IPS PADA MATERI CARA MENGHADAPI BENCANA ALAM DENGAN MENGGUNAKAN TEKNIK THE POWER OF TWO SISWA KELAS VIB SDN 010 TEMBILAHAN HULUKECAMATAN TEMBILAHAN HULU - Raja Jusniati (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
The research has been done due to low learning outcomes of IPS on “The Way to face up the Natural Disasters” material of class VI B SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu. This learning problem has been overcome by using “The Power of Two” technique. The formulation of the problem: Does the applying of “The Power of Two” technique can improve the learning outcomes of IPS on class VI B SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu? The purpose of the research is to improve the learning outcomes of class VI B SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu through “the Power of Two” technique. The research is expected to be the benefits for the researcher, students, school, and Dinas Pendidikan Kabupaten Indragiri Hilir. Based on the results of the research, the using of “The Power of Two” technique, the learning outcomes and student learning completeness of students of class VI B SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu are significantly increased. At the beginning, the absorption or pre-action is 41.90 (Very Bad); on cycle I is 69.04 (Middle); the result of cycle II is 95.23 (Very Good). Learning completeness has increased both individually and classically, the preliminary data of 4 students or 19.04 % (Not Completed Yet); on cycle I is 15 students or 69.04 % (Not Completed Yet); cycle II is 20 students or 95.23 % (Completed). KKM (70) is above 85 %. Based on The results of the observation of the observer and the researcher, the students of class VI B SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu seemed got the points through “The Power of Two” technique and they could cooperated in pair and more active while studying IPS. Based on the results of the research, the improvement of learning through “The Power of Two” technique is successful in improving the problem of low students learning outcomes of class VI B SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu year 2017/2018.